Business valuation of World Wide Web and new generation Media companies - Guichard, Paul (2019)
This thesis explores and provides insights on the issues encountered when performing the valuation of world wide web and new generation media companies, as the world wide web has precisely burst upon the businesses in contemporary times. The objectives are how to apprehend and identify the sometimes specific value drivers and their value-relevancy, study Internet business models and overall to identify the needed criteria for the valuation. As it is, the main challenges seem to be the oversight of the “immaterial” factors and the misunderstanding of techniques and data in a fast changing and highly uncertain industry. Thus, this paper will mitigate valuation methods in an attempt to determine the usefulness and relevancy of drivers, assumptions, and approaches while we study and compare the methods in the form similar as the SWOT analysis. In light of this, it appears that some are more significant than others when we also consider relevant non-financial indicators and the particularities of such companies.